ACTIVE REST AND STRETCHING BATIK DYEING WORKERS REDUCE MUSCULOSKELETAL COMPLAINTS AND INCREASE PRODUCTIVITY - Hermawan, Agung; Adiputra, Nyoman (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 8 No 1 (2022): Volume 8 No 1 Tahun 2022, 2022)
ABSTRACT Pekalongan is one of the largest batik-producing areas in Indonesia. Pekuncen Wiradesa Pekalongan batik coloring workers are 20 people with 10 people in the coloring section. The work process by standing bent over repeatedly for a long time causes musculoskeletal complaints in workers. The purpose of this study was to reduce musculoskeletal complaints and increase productivity in batik dye workers. This research is a true experimental type of research with the same subject design (treatment by subject design involving 10 workers. The sample in this study was set as control subjects and treatment subjects in different periods. In the period I workers worked as usual while period II worked by being given stretching and active rest every 2 hours after working for 6 days. Musculoskeletal complaints were measured by a Nordic body map questionnaire. Productivity was measured by calculating the time workers completed 200 clothes per day. Normality test of age data, BMI, working period, temperature, humidity, musculoskeletal complaints, productivity, and work pulse using Shapiro Wilk. Data analysis of musculoskeletal complaints, productivity, and work pulse used a statistical paired t-test with a value of 0.05. The results showed a significant difference p<0.05 in musculoskeletal complaints, the difference in period II was 11.3 or decreased by 6.43%, and was supported by a decrease in work pulse rate of 9.53%. Active rest and stretching increased productivity by 0.00117 or experienced a difference of 11.97%. It can be concluded that the application of ergonomics in the form of active rest and stretching reduces musculoskeletal complaints and increases productivity in Pekuncen Wiradesa Pekalongan batik coloring workers. Keywords: Active Rest, Stretching, Musculoskeletal Complaints, Work Productivity, Batik Dye